2015
DOI: 10.1155/2015/546106
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Risk Factors Associated with Tuberculosis Treatment Abandonment and Mortality

Abstract: Objectives. To identify the risk factors that were associated with abandonment of treatment and mortality in tuberculosis (TB) patients. Methods. This study was a retrospective longitudinal cohort study involving tuberculosis patients treated between 2002 and 2008 in a TB reference center. Results. A total of 1,257 patients were evaluated, with 69.1% men, 54.4% under 40 years of age, 18.9% with extrapulmonary disease, and 9.3% coinfected with HIV. The risk factors that were associated with abandonment of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
4
12
0
1
Order By: Relevance
“…In the study by Özkara et al in 108 dispensaries, the rate of extrapulmonary TB was reported to vary between 14.8% and 28.4% between provinces 34. In this study, although the rate of extrapulmonary TB was significantly lower in males, relapse cases and patients with a history of contact in the last decade, it was significantly higher in females14,35,36 and those younger than 15 years35 and most frequently showed pleura and lymph node involvement,30,37 similar to some domestic and foreign studies. In studies carried out in the United States and Brazil, drug resistance was reported to be low in extrapulmonary TB patients 30,36.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In the study by Özkara et al in 108 dispensaries, the rate of extrapulmonary TB was reported to vary between 14.8% and 28.4% between provinces 34. In this study, although the rate of extrapulmonary TB was significantly lower in males, relapse cases and patients with a history of contact in the last decade, it was significantly higher in females14,35,36 and those younger than 15 years35 and most frequently showed pleura and lymph node involvement,30,37 similar to some domestic and foreign studies. In studies carried out in the United States and Brazil, drug resistance was reported to be low in extrapulmonary TB patients 30,36.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, although the rate of extrapulmonary TB was significantly lower in males, relapse cases and patients with a history of contact in the last decade, it was significantly higher in females14,35,36 and those younger than 15 years35 and most frequently showed pleura and lymph node involvement,30,37 similar to some domestic and foreign studies. In studies carried out in the United States and Brazil, drug resistance was reported to be low in extrapulmonary TB patients 30,36. Extrapulmonary tuberculosis can be affected by comorbidities that cause immunodeficiency, such as HIV infection; patient characteristics; endocrine factors; immunological and genetic susceptibilities; and differences in endemic tuberculosis strains by population and geographical region, and these factors should be identified 30,35,36.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations